2003
DOI: 10.4049/jimmunol.171.12.6954
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Dampening of Anti-Islet Self-Reactivity but Promotion of Diabetes by OX40 Ligand

Abstract: Costimulatory signals received by diabetogenic T cells during priming by or upon secondary encounter with autoantigen are decisive in determining the outcome of autoimmune attack. The OX40-OX40 ligand (OX40L) costimulatory pathway is known to influence T cell responses, prompting us to examine its role in autoimmune diabetes. A null allele at OX40L completely prevented diabetes development in nonobese diabetic mice and strongly reduced its incidence in a TCR transgenic model (BDC2.5). However, somewhat paradox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…This possibility was supported by the findings of enhanced induction of Foxp3 ϩ T-cells when the OX40L/OX40 signaling pathway was blocked (G.B., S.G., G.D., A.A., unpublished data). Moreover, the involvement of the OX40/OX40L pathway in diabetes was consistent with previous reports of diabetes protection in NOD mice treated with anti-OX40L antibodies and in OX40L Ϫ/Ϫ NOD mice (49,50). These data suggested the important role of OX40/OX40L interaction in the differentiation of Tregs and the protection against diabetes observed here in TSLP-DCs transferred NOD mice.…”
Section: Discussionsupporting
confidence: 81%
“…This possibility was supported by the findings of enhanced induction of Foxp3 ϩ T-cells when the OX40L/OX40 signaling pathway was blocked (G.B., S.G., G.D., A.A., unpublished data). Moreover, the involvement of the OX40/OX40L pathway in diabetes was consistent with previous reports of diabetes protection in NOD mice treated with anti-OX40L antibodies and in OX40L Ϫ/Ϫ NOD mice (49,50). These data suggested the important role of OX40/OX40L interaction in the differentiation of Tregs and the protection against diabetes observed here in TSLP-DCs transferred NOD mice.…”
Section: Discussionsupporting
confidence: 81%
“…These results were supported by in vivo studies showing that blocking OX40͞OX40L interaction prevents the induction and maintenance of TH2-mediated allergic immune responses (21)(22)(23). However, other studies revealed that blocking OX40͞OX40L interaction ameliorates or prevents TH1-mediated diseases (24)(25)(26). Furthermore, administration of soluble OX40L or gene transfer of OX40L into tumors has been shown to strongly enhance antitumor immunity in mice (27,28).…”
Section: Discussionmentioning
confidence: 86%
“…This costimulatory pair is induced by IL-12, it is important for development and survival of memory CD4 ϩ T cells and is implicated in several autoimmune diseases including diabetes and multiple sclerosis, 78,79 and also in atherosclerosis. 80 Overexpression of Ox40L in fat-fed mice increased fatty streak formation, whereas Ox40L Ϫ/Ϫ mice exhibited smaller lesions than did controls.…”
Section: Ox40 and Ox40lmentioning
confidence: 99%